Implementation of Moral Values in the Social Life of Muslim Communities - Hasan, Hasan; Eko Nursalim; Nurona Abdi Ridhotullah; Ahmad Rawi; Nasir, Muhammad (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
Moral values are the main foundation in Islamic teachings that have a strategic role in shaping individual character and building a harmonious social order. This study aims to analyse how the implementation of moral values is applied in the social life of Muslim communities, both in the family environment, education, economy, and social interaction. Through a descriptive qualitative approach and literature study, it is found that noble morals such as honesty, trustworthiness, tolerance, responsibility, and social care are important pillars in fostering human relations. The role of the family, educational institutions, and community leaders is decisive in instilling and fostering the morals of the Muslim generation. However, the challenges of globalisation and digitalisation today often weaken moral values and strengthen individualistic culture. Therefore, strengthening moral education through integrative and exemplary approaches needs to be continuously developed so that Muslim communities can maintain their moral and social identity. This research recommends a synergy between formal education, family, and social environment in upholding moral values in the midst of changing times.